2013
DOI: 10.1152/ajprenal.00143.2013
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerulosclerosis is associated with aPDSS2haplotype and, independently, with a decreased content of coenzyme Q10

Abstract: JB. Focal segmental glomerulosclerosis is associated with a PDSS2 haplotype and, independently, with a decreased content of coenzyme Q 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 68 publications
0
27
0
1
Order By: Relevance
“…Should these findings extend beyond E. coli to other species and possibly other membrane-related stresses, it might be a promising approach to target stress-induced ubiquinone accumulation for the treatment of infectious and other diseases. For instance, recent studies have found that human patients suffering from nephrotic syndrome displayed reduced Q10 levels 42 , and a mutation in a Q10 biosynthetic enzyme in mice caused pathological symptoms similar to Parkinson's disease 43 . Finally, induction of Q8 accumulation by elevated salt levels might be an effective strategy for the biotechnological production of this or related compounds 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Should these findings extend beyond E. coli to other species and possibly other membrane-related stresses, it might be a promising approach to target stress-induced ubiquinone accumulation for the treatment of infectious and other diseases. For instance, recent studies have found that human patients suffering from nephrotic syndrome displayed reduced Q10 levels 42 , and a mutation in a Q10 biosynthetic enzyme in mice caused pathological symptoms similar to Parkinson's disease 43 . Finally, induction of Q8 accumulation by elevated salt levels might be an effective strategy for the biotechnological production of this or related compounds 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The RP-HPLC-MS/MS analyses were performed as previously described for determination of Q 6 in yeast lipid extracts ( 11,18 ) and determination of Q 9 and Q 10 in mammalian lipid extracts ( 28,29 ). Briefl y, a 4000 QTRAP linear MS/MS spectrometer from Applied Biosystems (Foster City, CA) was used.…”
Section: Rp-hplc-ms/msmentioning
confidence: 99%
“…A haplotype defined by two noncoding single-nucleotide polymorphisms in the PDSS2 gene was identified at an increased frequency in European American populations with FSGS, but not African American populations with FSGS. 58 Another interesting observation was that lymphoblastoid cell lines derived from individuals with FSGS had decreased coenzyme Q 10 content compared to cell lines from control populations without kidney disease, but this did not correlate with the PDSS2 haplotype. These results suggest that proteinuric kidney disease may contribute to a secondary form of coenzyme Q 10 deficiency that may occur through epigenetic mechanisms.…”
mentioning
confidence: 99%